Analysis of steel beam-column assemblies under column removal scenario with web opening beam - Nur Ain Ithnin , Alias (2012)
This paper present and discuss the fmite element method as an alternative method to investigate and analyze the steel beam-column with web opening assemblies under a column removal scenario. In this paper, analytical models produced in LUSAS Modeler for defining the deflections and stress due to vertically applied load. The steel structures assemblies are selected and analyzed for linear deflection and stress pattern when the column is removed. Four steel model assemblies were used. Two models were assembled by solid steel structure while the other two were with assembled with web opening beam structures. For both assemblies, the results taken before and after the column removed. The model with and without web opening were compared due to their strength and behaviour using Linear Finite Element Analysis. It was found that the model assemblies with web opening have lower results in terms of strength. The maximum load that it can withstand is the lowest of all assemblies especially when the center column is removed. The results of this study shows that the presence of web opening in structure may weakened the assembly of the structures itself.